1998
DOI: 10.1128/jvi.72.6.4643-4649.1998
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Glial Cells by the Human Polyomavirus JC Is Mediated by an N-Linked Glycoprotein Containing Terminal α(2-6)-Linked Sialic Acids

Abstract: The human JC polyomavirus (JCV) is the etiologic agent of the fatal central nervous system (CNS) demyelinating disease progressive multifocal leukoencephalopathy (PML). PML typically occurs in immunosuppressed patients and is the direct result of JCV infection of oligodendrocytes. The initial event in infection of cells by JCV is attachment of the virus to receptors present on the surface of a susceptible cell. Our laboratory has been studying this critical event in the life cycle of JCV, and we have found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(67 citation statements)
references
References 74 publications
2
59
0
3
Order By: Relevance
“…In contrast, JCV enters host cells by receptor-mediated clathrin-dependent endocytosis [28]. Furthermore, it has been reported that JCV does not share receptor specificity with SV 40 on human glial cells, because anticlass I antibodies failed to inhibit JCV infection [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, JCV enters host cells by receptor-mediated clathrin-dependent endocytosis [28]. Furthermore, it has been reported that JCV does not share receptor specificity with SV 40 on human glial cells, because anticlass I antibodies failed to inhibit JCV infection [6].…”
Section: Discussionmentioning
confidence: 99%
“…The cellular receptor molecule for JCV is unknown, but it has been reported to be an N-linked glycoprotein containing a2-6-linked sialic acids, based on the observation that a2-6-specific sialidase inhibits infection of glial cells by JCV. In addition, treatment of permissive cells with tunicamycin, which removes N-linked oligosaccharides, was shown to inhibit JCV infection in vitro [6]. These findings indicate that the interaction between the major structural protein VP1 and sialic acids is critical for JCV infectivity.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Both of the human polyomaviruses require sialic acid to infect cells. JCV can use either an α2,3or an α2,6-linked sialic acid to infect permissive glial cells (Dugan et al, 2007;Liu et al, 1998) and a ganglioside (GT1b) may also be involved (Komagome et al, 2002) (Table 1). BKV uses only the α2,3-linkage to infect cells (Dugan et al, 2005) (Table 1).…”
Section: Jcv and Bkvmentioning
confidence: 99%
“…Is JCV host cell restriction at the level of binding and entry or is it at the molecular level? The recent identiWcation of the speciWc cell surface receptor for JCV has provided some answers to these questions (Liu et al, 1998). The receptor, an a 2-6 linked sialic acid, is a commonly expressed ganglioside found on the surface of various cells.…”
Section: Jc Virusmentioning
confidence: 99%